Financial needs and tools for agricultural development and transformation pertinent to low-income, food-insecure countries - Alexandros Sarris (Fondation pour les études et recherches sur le développement international (FERDI), 2016)
The process of agricultural transformation is discussed, and the role of agriculture in both growth and poverty reduction is reviewed. The finance needs for agricultural development in low income food insecure countries is discussed, and the public and other official flows to agricultural development reviewed. It is seen that the monetary flows into agriculture have been grossly inadequate, compared to needs. The situation of smallholders is reviewed, and their financing needs are explored. It is indicated that the current finance flows to smallholders are less than 5 percent of perceived needs. A variety of institutional methods and models for increasing agricultural smallholder finance are then reviewed and assessed.
Keywords: 330